Tailoring Electron‐Riched Boron Sites in BCN for Nitrogen Fixation via Alternate Mechanism. Issue 5 (10th January 2022) - Yang, Yutong; Wang, Yin; Wang, Xia; Chen, Shaoqing; Duan, Limei; Zhang, Wei; Li, Wanfei; Liu, Jinghai
Abstract: The electrochemical nitrogen reduction reaction (eNRR) is promising for achieving sustainable ammonia (NH3 ) production under mild conditions. However, it is still challenged by nitrogen activation and strong competition with the hydrogen evolution reaction. Here, it is revealed that fine‐tuning the local electron density of boron (B) sites at the boron carbon nitride (BCN) solid catalysts has significant effects on the eNRR activity and selectivity. The concentration of electron‐rich B sites at BCN catalysts are mediated by solid‐state reaction, where their electronic structures are confirmed by electron energy‐loss spectroscopy (EELS) and electron paramagnetic resonance (EPR). Over the density functional theory (DFT) calculations, the nitrogen (N2 ) activation and reduction at an electron‐riched B site is through an alternate pathway with the determining‐step energy of only 0.92 eV. The optimized BCN5 catalyst with the highest ratio of electron‐riched B sites achieves an outstanding NH3 production rate of 29.3 µg h −1 mg −1 cat and the highest Faradaic efficiency of 39%. Abstract : The local electron density of B sites is significant to the N2 adsorption, NN bond activation and the selectivity of reaction pathway during electrochemical nitrogen reduction reaction (NRR) process. The electron‐riched boron sites at metal‐free boron carbon nitride would provide an excellent electrocatalytic activity and selectivity for NRR under ambient conditions.